The Scope and Method of Economics - Lange, O. (Review of Economic Studies, 1945)
Journal Article The Scope and Method of Economics Get access O. Lange O. Lange Washington, D.C. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 13, Issue 1, 1945, Pages 19–32, https://doi.org/10.2307/2296113 Published: 01 April 1945